Pelatihan Akuntansi Sederhana Bagi Umkm Di Kecamatan Taba Penanjung - Kresnawati, Kresnwati; Herlyaminda, Evi; Hanila, Siti; Rahayu, Hesti Riski; Lubis, Wildhan Rivaldo (Universitas Dehasen Bengkulu, 2025)
MSMEs are a sector that supports 97% of the workforce in the Republic of Indonesia, however many MSMEs do not carry out proper accounting records. Several underlying factors include an incorrect financial reporting mindset, limited knowledge of financial management and accounting and limited time and energy. Simple accounting recording training is a solution to help MSMEs manage their finances more regularly and bankably. Accounting training carried out for 30 MSMEs in Taba Penanjung sub-district, Bengkulu Regency is being carried out in one day as a form of community service, receiving a positive and enthusiastic response from the training participants and providing quite a positive impact based on the pretest and posttest. MSME players with various educational backgrounds are considered quite capable of understanding the basic equations of accounting and financial reports such as balance sheets, profit and loss and notes to financial reports (CaLK) in a simple manner. Further assistance, not limited to training, is a recommendation for this simple accounting recording training activity.